Integration of the POE Model and Metaphoral Thinking in Student Worksheets: Improving Mathematical Reasoning Abilities in the Modern Education Era - Endra, Karyawati; Villaflor, Gillian Mae (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This research aims to develop and evaluate the effectiveness of POE-based (Predict, Observe, Explain) student worksheets using a metaphorical thinking approach to enhance the mathematical reasoning abilities of class 9 students at Public Middle School. Methodology: This research aims to find out how to develop student worksheets based on POE (Predict, Observe, Explain) through a metaphoral thinking approach oriented towards the mathematical reasoning abilities of junior high school students in class 9 and find out the effectiveness of student worksheet products based on POE (Predict, Observe, Explain) through Metaphoral Thinking approach to the mathematical reasoning abilities of Public Middle School 7 Banjit students in class 9. Main Findings: Validation results showed material experts rated the worksheets at 89.4%, media experts at 94.9%, and language experts at 75%, all with high appropriateness. Small group trials averaged 86%, field trials 87%, and educator trials 97.2%, all with very good criteria. The paired t-test (thitung = 12.7 > ttabel = 2.02) confirmed the effectiveness of the POE-based worksheets using the Metaphorical Thinking approach in enhancing mathematical reasoning abilities.. Novelty/Originality of this study: The novelty of this study lies in developing and validating POE-based student worksheets integrated with a metaphorical thinking approach to enhance junior high students' mathematical reasoning. This innovative strategy combines cognitive and imaginative techniques, fostering deeper comprehension and problem-solving skills.